'End the dominance of the Uyghur ethnic group': an analysis of Beijing's population optimization strategy in southern Xinjiang. Issue 3 (3rd July 2021) - Zenz, Adrian
ABSTRACT: Chinese academics and politicians argue that Xinjiang's 'terrorism' problem can only be solved by 'optimizing' its ethnic population structure. High ethnic minority population concentrations are considered a national security threat. 'Optimizing' such concentrations requires 'embedding' substantial Han populations, whose 'positive culture' can mitigate the Uyghur 'human problem'. Scenarios that do not overburden the region's ecological carrying capacity entail drastic reductions in ethnic minority natural population growth, potentially decreasing their populations. Population 'optimization' discourses and related policies provide a basis to assess Beijing's 'intent' to destroy an ethnic minority population in part through birth prevention per the 1948 United Nations Genocide Convention. The 'destruction in part' can be assessed as the difference between projected natural population growth without substantial government interference and reduced growth scenarios in line with population 'optimization' requirements. Based on population projections by Chinese researchers, this difference could range between 2.6 and 4.5 million lives by 2040.